2021
DOI: 10.1111/codi.15934
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic positron emission tomography/CT response after induction chemotherapy and chemo(re)irradiation is associated with higher negative resection margin rate in patients with locally recurrent rectal cancer

Abstract: Aim Positron emission tomography (PET)/CT can be used to monitor the metabolic changes that occur after intensified treatment with induction chemotherapy and chemo(re)irradiation for locally recurrent rectal cancer (LRRC). This study aimed to analyse the correlation between the PET/CT response and final histopathological outcomes. Methods All LRRC patients who underwent induction chemotherapy prior to surgery between January 2010 and July 2020 and were monitored with pretreatment and post‐treatment PET/CT were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Therefore, comparison of repeated high-quality imaging would be the way forward. In two recently published studies from the authors' centre 30,31 , the response after neoadjuvant treatment on imaging was analysed and compared with the pathological response. These studies showed that response evaluation was indeed more challenging in LRRC than in LARC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, comparison of repeated high-quality imaging would be the way forward. In two recently published studies from the authors' centre 30,31 , the response after neoadjuvant treatment on imaging was analysed and compared with the pathological response. These studies showed that response evaluation was indeed more challenging in LRRC than in LARC.…”
Section: Discussionmentioning
confidence: 99%